Is Party Type Relevant to an Explanation of Policy Congruence? Catch-all versus Ideological Parties in the Portuguese Case - Belchior, Ana Maria (2013)
Most research on policy congruence has failed to provide an explanation for it. Party characteristics are acknowledged to be relevant, but the literature has not achieved a consensus as to their effective importance. Nor has there thus far been an analysis of the implications for results of using different methods to assess congruence. The present article seeks to test the importance of party type (catchall versus ideological) for an explanation of levels of intra-party congruence, with a control using the main congruence-assessment methods. The article focuses on the Portuguese party system and makes use of a set of 19 policy issues across two dimensions: socioeconomic left–right and libertarian–authoritarian (plus left–right self-placement), which introduces additional controls of the assessment of party-type relevance. As far as we know, such an in-depth analysis of party-type congruence has not been done before. Findings support the notion that Portuguese catchall parties tend to display higher levels of MP–voter congruence than ideological parties, but the type of policy issue is also relevant: levels of congruence diverge across parties depending on the issue at stake. These results were supported by the different methods used.